2019
DOI: 10.1111/apha.13278
|View full text |Cite
|
Sign up to set email alerts
|

miR‐29c improves skeletal muscle mass and function throughout myocyte proliferation and differentiation and by repressing atrophy‐related genes

Abstract: AimTo identify microRNAs (miRs) involved in the regulation of skeletal muscle mass. For that purpose, we have initially utilized an in silico analysis, resulting in the identification of miR‐29c as a positive regulator of muscle mass.MethodsmiR‐29c was electrotransferred to the tibialis anterior to address its morphometric and functional properties and to determine the level of satellite cell proliferation and differentiation. qPCR was used to investigate the effect of miR‐29c overexpression on trophicity‐rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 65 publications
4
44
0
Order By: Relevance
“…Ectopic expression of miR‐29c in C2C12 myoblasts enhanced myotube fusion and expression of myogenic markers. In addition, they reported that miR‐29c mimic inhibited the expression of the muscle atrophy‐related factors MuRF1, Atrogin‐1 and HDAC4 and provided evidence that miR‐29c targets MuRF1 transcript by binding directly to its 3′‐untranslated region (3′UTR) . These findings highlight the important role of microRNAs (miRNAs) in regulation of muscle homeostasis and indicate miR‐29c as a possible candidate for future therapeutic application in diseases involving decreased skeletal muscle mass.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Ectopic expression of miR‐29c in C2C12 myoblasts enhanced myotube fusion and expression of myogenic markers. In addition, they reported that miR‐29c mimic inhibited the expression of the muscle atrophy‐related factors MuRF1, Atrogin‐1 and HDAC4 and provided evidence that miR‐29c targets MuRF1 transcript by binding directly to its 3′‐untranslated region (3′UTR) . These findings highlight the important role of microRNAs (miRNAs) in regulation of muscle homeostasis and indicate miR‐29c as a possible candidate for future therapeutic application in diseases involving decreased skeletal muscle mass.…”
mentioning
confidence: 93%
“…Silva and colleagues give an important contribution in this regard. Indeed, they report that miR‐29c‐overexpressing mouse muscles showed increased size and length, including a higher number of serial sarcomeres, have no sign of inflammatory infiltration and generate more force, resulting in a positive adaptive response . These in vivo findings correlate with increased expression levels of differentiation specific markers and increased size of C2C12‐derived myotubes.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…1,2 The growth and development of skeletal muscle affect life activities, and patients with many pathological conditions show abnormal muscle development, such as immobilization after fracture, Duchenne muscular dystrophy (DMD) and Facioscapulohumeral muscular dystrophy. 1,2 The growth and development of skeletal muscle affect life activities, and patients with many pathological conditions show abnormal muscle development, such as immobilization after fracture, Duchenne muscular dystrophy (DMD) and Facioscapulohumeral muscular dystrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle plays a crucial role in providing movement and maintaining posture. 1,2 The growth and development of skeletal muscle affect life activities, and patients with many pathological conditions show abnormal muscle development, such as immobilization after fracture, Duchenne muscular dystrophy (DMD) and Facioscapulohumeral muscular dystrophy. [3][4][5][6][7][8] The formation of skeletal muscle is known as myogenesis and requires the fusion of myoblasts to produce multinucleated fibres.…”
Section: Introductionmentioning
confidence: 99%